Analysis of Safety Climate in Construction of Coal Fired Steam Power Plant (CFSPP) X with Capacity 2x1000 MW - Kasianto; Fatma Lestari (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Power plant construction process is complex with a lot of labor, machines and flammable materials, and the work carried out has high risk such as lifting, working at height, hot work such as welding, grinding, cutting and other activities that have a high risk. Objective: The objective of the research is to find out the overall picture of Work Safety Climate at CFSPP X and picture of Safety Climate at the Work and Personal level. Method: The design of this research is quantitative method, 58 questions by Zou & Sunindijo's Safety Climate framework in research of Fatma Lestari, et, al. 2020. Result: The description of the working Safety Climate of CFSPP X from 6 Dimension of Safety Climate are, Management Commitment mean is 3.92, Communication mean is 3,91, Training mean is 3,89, Personal Accountability mean is 3,87, Rule and Safety Procedure mean is 3,92, Supportive Environment mean is 3,90. The description of the Safety Climate at work and personal levels is good, with scores for all dimensions more than >3.30. There were 3 statements that received disagree answer from several respondents, which are: I report people who ignore safety procedures, 23 respondents, my responsibility is to work safely, including reporting colleagues who are not working safely, 5 respondents. There are punishments for unsafe behavior, 14 respondents. The Safety Climate dimension with the highest score is Management Commitment and Roles & Safety Procedure. Conclusion: The description of the Work Safety Climate, both at work and personal level, is good with score of more than >3.30. Disagree answer from several respondents was related to not wanting to report people who ignore safety procedures because there is punishment for unsafe behavior. The Safety Climate dimension with the highest score is Management Commitment, and for work attributes, both work and personal, Management Commitment and Rule & Safety Procedure dominate the highest average score.